특수교사 자격제도 상 명칭의 적절성에 대한 문헌 및 법률 검토 - 임이삭(Lim, Issac); 김지연(Kim, Jiyeon) (특수교육논총, 2024)
연구목적: 본 연구는 특수교육을 담당하고 있는 교사(이하, 특수교사)에 대한 교원자격제도 상의 명칭인 ‘특수학교 교사’ 의 적절성에 대해 탐색하는 것을 목적으로 하였다. 연구방법: 연구목적을 달성하기 위하여 특수교사의 자격제도 명칭을 규정하고 있는 연혁 법령 분석, 논문과 보고서 등의 문헌 분석 및 현행법의 검토를 실시하였다. 연구결과: 첫째, 특수교사 자격제도의 명칭은 1953년부터 1963년, 1973년부터 1978년까지 ‘특수교사’로, 그 외의 시기는 ‘특수학교 교사’로 사용되었다. 둘째, 특수교사 자격제도 상 명칭을 연구의 중심 주제로 다룬 문헌은 없었고, 특수교사 양성체제 및 교육과정을 다룬 연구의 하위 내용으로 다루고 있었다. 현행 명칭인 ‘특수학교 교사’의 적절성에 대한 찬⋅반 주장과 주장에 대한 근거가 제시되어 왔으며, 문헌마다 입장은 상이하였다. 셋째, 현행 법령을 검토한 결과 ① 현행「초⋅중등교육법」에서 규정하고 있는 교사의 자격 명칭, 특히 정교사 및 준교사의 명칭이 교육을 위하여 설립된 기관 내지 장소의 명칭을 사용하고 있어 체계상 적절하지 않다는 점, ② 특수교육은 특수학교 외의 장소에서도 이루어지고 있고, 현행 명칭이 특수교육에 종사하고 있는 교사의 지위와 전문성을 적절하게 반영하지 못하고 있다는 점을 확인하였다. 넷째, ‘특수학교 교사’ 자격 명칭의 재정립을 위해 특수교사를 별도의 교사로 규정하는 것이 필요하고, 자격 명칭 문제 해결을 위한 입법적 방안을 제안하였다. 결론: 연구 결과를 근거로 현재 특수교육에 종사하는 교사의 지위와 전문성을 적절하게 반영할 수 있도록 교사 자격의 명칭이 정비되어야 한다. Purpose: This study investigated the appropriateness of the term “special school teacher” under the teacher qualification system for educators responsible for special education, hereafter referred to as special education teachers. Method: The study involved a literature review of historical legislation, studies, and reports, alongside a legal review of current legislation. Result: Several key findings emerged. First, the designation for special education teachers varied over time, with “special teacher” used from 1953 to 1963 and from 1973 to 1978, while “special school teacher” was employed during other periods. Second, there is a lack of literature specifically addressing the title of special education teachers; instead, it is often treated as a secondary topic in studies focusing on the special education teacher training system and curriculum. Evidence has been presented both for and against the appropriateness of the current term “special school teacher,” and each document had a different position. Third, the current legislative system governing the qualifications of special school teachers was examined, issues were discovered, and legal solutions were proposed to address them. Conclusion: The study concluded that the current designation “special school teacher” for qualifications is not definitive and should be adjusted to align with evolving societal requirements. Additionally, the identification of issues within the legal framework prompted the proposals for solutions. As a result, it is recommended to revise the designation for teacher qualifications to more accurately reflect the status and expertise of teachers currently engaged in special education. KCI Citation Count: 0